Proceedings of the 13th International Joint Conference on Biomedical Engineering Systems and Technologies 2020
DOI: 10.5220/0008971104720481
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Patients’ Location Data to Support the Application of Process Mining Notations

Abstract: The application of indoor localization and process mining emerges as an intriguing tool for the researchers to address the structural issues related to the patient pathways inside healthcare organizations. However, there is a major gap in the literature. This is related to the lack of enough attention to the interpretation of location data. Therefore, as a contribution, this article presents the DIAG meta-model and relevant location data interpretation rules. This model-driven approach has been realized in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(40 reference statements)
0
3
0
1
Order By: Relevance
“…We focus on analyzing patients in the urology department. To better understand how the data was inter-preted and prepared for process discovery actions, we refer to the works in [32,33]. • Sepsis Data set [34]: This event log consists of sepsis cases in a hospital.…”
Section: Case Studies: Discussion and Evaluationmentioning
confidence: 99%
“…We focus on analyzing patients in the urology department. To better understand how the data was inter-preted and prepared for process discovery actions, we refer to the works in [32,33]. • Sepsis Data set [34]: This event log consists of sepsis cases in a hospital.…”
Section: Case Studies: Discussion and Evaluationmentioning
confidence: 99%
“…Locations are determined by means of wireless technologies as radio frequency identification (RFID) tags, integrated in patient identification bands or staff cards, and antennas which are deployed in the hospital's departments. RTLS data have been used for PM to collect patients' movements (Araghi et al, 2019(Araghi et al, , 2020Araghi, Fontaili, et al, 2018;Araghi, Fontanili, et al, 2018;Fern andez-Llatas et al, 2013;Martinez-Millana et al, 2019), to mine the workflow of medical equipments (Liu et al, 2014), to study a surgical process (Fernandez-Llatas et al, 2015), and to enhance event logs extracted from a HIS (Fernandez-Llatas et al, 2021;Martin, 2018).…”
Section: Healthcare Datamentioning
confidence: 99%
“…Automated (Abo-Hamad, 2017; Alharbi et al, 2018;Alvarez et al, 2018;Amantea et al, 2020;Antonelli & Bruno, 2015;Araghi et al, 2020;Araghi, Fontaili, et al, 2018;Baker et al, 2017;Bouarfa & Dankelman, 2012;Caron et al, 2011;Caron et al, 2014;B. Chen et al, 2021;Chiudinelli et al, 2020;Cho et al, 2014;Dagliati et al, 2014;De Oliveira et al, 2020;De Weerdt et al, 2012;Duma & Aringhieri, 2020;Fei et al, 2010;Fernandez-Llatas et al, 2015;Fern andez-Llatas et al, 2010;Fern andez-Llatas, Garcia-Gomez, et al, 2011;Furniss et al, 2016;Garg & Agarwal, 2016;A.…”
Section: Discovery Approach Referencesunclassified
“…Looking at C2 and C3 in Table 1, it is important for process mining applications to provide extended information about healthcare processes, such as causes of drifts and deviations in processes. Research has shown that diagnosing inefficiencies and reasoning in healthcare processes are often ignored [5][6][7].…”
Section: Introductionmentioning
confidence: 99%